1995
DOI: 10.1212/wnl.45.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of GABAergic neurons in the basal ganglia of patients with progressive supranuclear palsy

Abstract: We analyzed postmortem GABAergic neurons in the basal ganglia of three patients with progressive supranuclear palsy (PSP) and four matched controls by means of glutamic acid decarboxylase (M(r) 67,000 [GAD67]) mRNA in situ hybridization. In PSP, we found a 50 to 60% decrease in the number of neurons expressing GAD67 mRNA in the caudate nucleus, ventral striatum, and the external and internal pallidum. The expression of GAD67 mRNA per neuron was reduced in the caudate nucleus and putamen (-43%), the ventral str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 57 publications
(4 reference statements)
2
31
0
Order By: Relevance
“…55 Because PV+ GPe neurones are known to project to the output nuclei and the subthalamus, 41 a selective reduction in their inhibitory activity in association with a loss of the excitatory drive from the subthalamus would give rise to an increase in thalamic inhibition and produce parkinsonian hypokinetic symptoms, fitting well with current theories of basal ganglia pathophysiology. 11,12 Pathology in the caudate and putamen could also contribute to the hypokinetic symptoms observed in PSP.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…55 Because PV+ GPe neurones are known to project to the output nuclei and the subthalamus, 41 a selective reduction in their inhibitory activity in association with a loss of the excitatory drive from the subthalamus would give rise to an increase in thalamic inhibition and produce parkinsonian hypokinetic symptoms, fitting well with current theories of basal ganglia pathophysiology. 11,12 Pathology in the caudate and putamen could also contribute to the hypokinetic symptoms observed in PSP.…”
Section: Discussionmentioning
confidence: 61%
“…There have been relatively few anatomic or pathologic studies of the GPe in people [53][54][55][56][57][58][59][60][61] and none analyzing changes in calcium-binding proteins. In this study, we have shown that the GPe of control subjects contains approximately 1.45 million neurones.…”
Section: Discussionmentioning
confidence: 99%
“…The neurodegenerative changes in the striatum may result in a net loss of GABAergic neurons within the basal ganglia (Levy et al, 1995). There is a pronounced decrease in dopaminergic nerve terminals in the caudate and putamen of patients with PSP (Filippi et al, 2006), which may arise from loss of inputs from substantia nigra (Warren et al, 2007) and ventral tegmentum in the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…2C,D). We examined G␣olf levels in patients with another disease of basal ganglia, progressive supranuclear palsy (PSP), which shares with PD a severe dopaminergic denervation but includes degeneration of additional neuronal populations (Levy et al, 1995). An increase in G␣olf levels was also observed in the putamen of five patients with PSP, although it was less pronounced than in PD and did not reach statistical significance ( Fig.…”
Section: G␣olf Is Prominently Expressed In Human Striatummentioning
confidence: 99%